Living in a limbo between two homes. (c2019) - Khafaji, Lana (2019)
As a result of the Syrian crisis which began in 2011, Lebanon has been a main country of refuge for a large number of Syrian refugees. According to the annual report from the Danish Refugee Council (2016), 25% of Lebanon’s population are refugees. This has led to serious concerns on the issue of their return. Interdisciplinary scholars from different backgrounds have discussed the concept of repatriation, however, there has been a lack of scholarly research on the return of Syrian refugees in Lebanon to their home. This paper aims to study the challenges of repatriation of Syrian refugees and examine whether they consider Lebanon as their second home. In my study, I will assess their living conditions in Lebanon and their everyday ordeals based a number of semi-structured interviews I have conducted with them. Collected data are crossreferenced and analyzed with the general concept of repatriation that has been discussed by scholars. Basically, it is found that the return to Syria is not happening in the near future, and some refugees have found a second home in Lebanon due to the severe losses they have faced after the 2011 war on Syria. Studies that have been conducted for this project state that Syrian refugees portray the return to their homeland as a ‘myth’ because the nostalgic feeling for Syria that they once knew is no longer there.